Implementation of Enhanced Energy Buffer Aware Reliable Routing Protocol in MANETS - G, Murali; Swami, Apoorva M; Kadam, Kruthika G; G, Kusuma; Katwey, Mandakini A (International Journal of Computer Sciences and Engineering, 2025)
Mobile ad hoc networks (MANET) are one of the most significant emerging research areas in wireless communication. Nodes in MANET undergo continuous self-configuration where power awareness is an essential issue to improve the communication for all the nodes. MANET nodes are miniature devices with limited energy, transmission range, memory and computational power. The energy efficient routing is one of the most important design criteria for MANETS, since mobile nodes will be powered by batteries with limited capacities. Power failure of a mobile node not only affects the node itself but also its ability to forward packets on behalf of others and thus affects the overall network life-time. Due to this, we propose a novel protocol called ENHANCED ENERGY BUFFER AWARE RELIABLE ROUTING (EEBARR) in WSN with more number of nodes to transmit the packets from source to destination. It improves the packet transmission, balances the energy and uses buffer management policy to mitigate packet losses and analyze the performance using the parameters like Energy consumption, Throughput, Packet delivery ratio, End to End delay and Reliability.